Peningkatan Motorik Halus Anak Melalui Media Box Pintar Pada Kelas B2 TK Pertiwi I Muara Bungo - Uswatul Hasni; Astri Octavia; Fatmawati; Widi Amira (CV. ITTC INDONESIA, 2024)
Children's ability to improve fine motor skills is still low. Lack of variety in teachers in providing learning. The aim of classroom action research is to improve children's fine motor skills through the activity of sewing picture patterns on smart boxes. The type of research is classroom action research, namely research that aims to improve the quality of learning in the classroom and improve the learning process carried out. Research data through observation, interviews. The research was carried out in two cycles. In cycle II, children's fine motor skills increased